PENGARUH PEMBERIAN PUPUK KASCING DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Var saccharata Sturt) - Dailami, Ahmad; Yetti, Husna; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sweet corn (Zea mays Var saccarata Sturt) widely used because it has the nutrients and relatively high levels of sugar so it tastes sweeter than regular corn. Fertilization is one of the important agronomic aspects considered as closely related to the planting medium, for that is necessary for soil fertilization can provide nutrients needed by plants sweet corn so that the results can be maximized. This study aimed to determine the effect of vermicompost and NPK fertilizer on the growth and yield of sweet corn and get the best treatment effect. Research conducted at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru. The study conducted from May to August 2014. The study was carried out experiments using a randomized block design (RBD) factorial consisting of two factors, namely vermicompost and NPK fertilizer with 3 replications. Parameters measured were plant height, harvest age, weight cornhusk cob, cob weight without husk, production per plot, circumference cob and length cob. The results showed vermicompost and NPK significantly affected all parameters were observed. Doses vermicompost 4 tons/ha and 250 kg NPK/ha gives the best results on the growth and yield of sweet corn compared with other treatments. Keyword: NPK fertilizer, sweet corn, vermicompos